FAKTOR-FAKTOR YANG MEMPENGARUHI KETIDAKPATUHAN MINUM OBAT PADA PASIEN TUBERKULOSIS PARU - YULY ABDI ZAINURRIDHA (Program Studi Keperawatan dan Kesehatan, Sekolah Tinggi Ilmu Kesehatan (STIKES) Bhakti Al-Qodiri, 2022)
Background: Pulmonary tuberculosis is a contagious infectious disease caused by bacteria, which can attack the respiratory system, namely the lungs. This disease every year accounts for the highest number of deaths in the world, including developing countries. To achieve successful treatment, patients must be patient to take TB drugs to completion.Methods: This study uses a correlation approach. a total of 20 respondents with pulmonary tb, using the total sampling technique. Kai kuadrat data analysis.Result: There was a significant effect between education, knowledge, length of illness, and side effects of drugs with a value (p < 0.05).Conclusion: Education, knowledge, length of illness, and side effects of drugs have a significant effect on uncompliance to taking medication in pulmonary tb patients in the kapongan health center work area